الشيخ محمد مختار بن عطارد البوغوري الجاوي ثم المكي (1868—1930 م) دن جارينغان علماء سوندا تيمور تنغاه أول أبد 20 م - Sya'ban, Ginanjar Ahmad (INC- Islam Nusantara Center, 2018)
This paper intends to study about Syaikh Muhammad Mukhtâr ibn ‘Athârid al-Bughûrî al-Jâwî tsumma al-Makkî (1862-1930), oneof the important scholar who taught at Makkah al-Mukarramah in the early 20th century. This scholar came from Tatar Pasundan(West Java) in Nusantara, precisely from Bogor. Therefore, his name is attributed “al-Bûghûrî al-Jâwî” (from Bogor-Nusantara). Amongsthis students who came from Nusantara, he was popular as Shaykh Mukhtar Bogor or Guru Mukhtar Bogor. His figure can be referredas “the masters of Sundanese scholars who teach at Masjidil Haram”.Futhermore, this paper will also highlights the intellectual works of Shaykh Muhammad Mukhtâr ‘Athârid al-Bûghûrî. The works werewritten by him during his period of stay in Makkah and published in several publishers of the Middle East. Al-Bûghûrî wrote his works inArabic and Sundanese (Arabic in writing) in various fields, ranging from theology (‘aqîdah), jurisprudence (fiqh), astronomy, hadith, andtasawwuf. The works became more interesting because it could be a list of “treasures of Sundanese texts found in the Middle East”. It is hoped that the information presented about the figure of Shaykh Muhammad Mukhtâr ‘Athârid al-Bûghûrî, an ajengan Sunda, whobecame a professor at the Grand Mosque in Makkah, as well as his intellectual works and his contributions in Islamic civilization, aresufficiently representative through this paper . In addition, the study of this paper is also expected to provide a new perspective for the history ofthe Sundanese intellectual movement in the Middle East as well as the literary treasures and the Sundanese-Islamic texts in the region.